Multi-Day Prolonged Low- to Moderate-Intensity Endurance Exercise Mimics Training Improvements in Metabolic and Oxidative Profiles Without Concurrent Chromosomal Changes in Healthy Adults - Gagnon, Dominique D.; Dorman, Sandra; Ritchie, Stephen; Mutt, Shivaprakash Jagalur; Stenbäck, Ville; Walkowiak, Jarosław; Herzig, Karl-Heinz (Frontiers in Physiology, 2019)
Background: Oxidative stress results in lipid, protein and DNA oxidation, resulting in telomere erosion, chromosomal damage, and accelerated cellular aging. Training promotes healthy metabolic and oxidative profiles whereas the effects of multi-day, prolonged and continuous exercise, are unknown. This study investigated the effects of multi-day prolonged exercise on metabolic and oxidative stress as well as telomere integrity in healthy adults. Methods: Fifteen participants performed a 14-day, 260-km, wilderness canoeing expedition (12 males) (EXP) (24 ± 7 yrs, 72 ± 6 kg, 178 ± 8.0 cm, 18.4 ± 8.4 %BF, 47.5 ± 9.3 mlO2·kg-1·min-1), requiring 6-9 hrs of low- to moderate-intensity exercise daily. Ten controls participated locally (7 males) (CON) (31 ± 11 yrs, 72 ± 15 kg, 174 ± 10 cm, 22.8 ± 10.0 %BF, 47.1 ± 9.0 mlO2·kg-1·min-1). Blood plasma, serum, and mononuclear cells were sampled before and after the expedition to assess hormonal, metabolic, and oxidative changes. Results: Serum cholesterol, high- and low-density lipoprotein, testosterone, insulin, sodium, potassium, urea and chloride concentrations were not different between groups, whereas triglycerides, glucose, and creatinine levels were lower following the expedition (p < 0.001). Malondialdehyde and relative telomere length were unaffected (EXP: 4.2 ± 1.3 vs. CON: 4.1 ± 0.7 µM; p > 0.05: EXP: 1.00 ± 0.48 vs. CON: 0.89 ± 0.28 TS ratio; p = 0.77, respectively); however, superoxidase dismutase activity was greater in the expedition group (3.1 ± 0.4 vs. 0.8 ± 0.5 U·ml-1; p < 0.001). Conclusion: These results indicate a modest improvement in metabolic and oxidative profiles with increased superoxidase dismutase levels, suggesting an antioxidative response to counteract the exercise-associated production of free radicals and reactive oxygen species during prolonged exercise, mimicking the effects from long-term training. Although improved antioxidant activity may lead to increased telomere length, the present exercise stimulus was insufficient to promote a positive cellular aging profile with concordant chromosomal changes in our healthy and young participants.